2022
DOI: 10.1016/j.molmet.2021.101405
|View full text |Cite
|
Sign up to set email alerts
|

Conditional gene targeting using UCP1-Cre mice directly targets the central nervous system beyond thermogenic adipose tissues

Abstract: Objective Uncoupling protein 1 (UCP1) is a mitochondrial protein critical for adaptive thermogenesis in adipose tissues, and it is typically believed to be restricted to thermogenic adipose tissues. UCP1-Cre transgenic mice are utilized in numerous studies to provide “brown adipose-specific” conditional gene targeting. Here, we examined the distribution of Cre and UCP1 throughout the body in UCP1-Cre reporter mice. Methods UCP1-Cre mice crossed to Ai14-tdTomato and Ai9-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 41 publications
2
29
1
Order By: Relevance
“…While previously the presence of other members of the UCP family of proteins in the brain has been affirmed and a role in neuronal function been demonstrated (for review, see Andrews et al, 2005 ), UCP-1 expression in the mouse brain ( Lengacher et al, 2004 ; Wang et al, 2019 ) has remained contradictory. However, a recent study using UCP1-cre reporter mice convincingly delineated the active expression of UCP1 in the mouse brain, with abundant levels of UCP-1 in the VMH and the amygdala ( Claflin et al, 2022 ). Indeed, in the present study we also confirmed UCP-1 expression in the hypothalamus of WT mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previously the presence of other members of the UCP family of proteins in the brain has been affirmed and a role in neuronal function been demonstrated (for review, see Andrews et al, 2005 ), UCP-1 expression in the mouse brain ( Lengacher et al, 2004 ; Wang et al, 2019 ) has remained contradictory. However, a recent study using UCP1-cre reporter mice convincingly delineated the active expression of UCP1 in the mouse brain, with abundant levels of UCP-1 in the VMH and the amygdala ( Claflin et al, 2022 ). Indeed, in the present study we also confirmed UCP-1 expression in the hypothalamus of WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…Also UCP-1, which originally was thought to be restricted to adipose tissues, is found in the brain, with significant expression in the ventromedial hypothalamus (VMH) and the amygdala ( Claflin et al, 2022 ), regions involved in both temperature and emotional control processes ( Charmandari et al, 2005 ; Morrison, 2016 ; Soto et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…An augmented DISCO protocol was utilized to clear whole brain tissue of Fgf21 -P2A-CRE; Ai14-tdTomato and CRE negative control mice as previously described ( Claflin et al, 2022 ). Mice were anesthetized and transcardially perfused with pH 9.5 saline followed by pH 9.5 4% PFA.…”
Section: Methodsmentioning
confidence: 99%
“…The average of fEPSP slopes from the first 20 min of baseline recording was used to normalize the data and ''n'' refers to slices. Tissue clearing, imaging, and processing An augmented DISCO protocol was utilized to clear whole brain tissue of Fgf21-P2A-CRE; Ai14-tdTomato and CRE negative control mice as previously described (Claflin et al, 2022). Mice were anesthetized and transcardially perfused with pH 9.5 saline followed by pH 9.5 4% PFA.…”
Section: Extracellular Recordingsmentioning
confidence: 99%
“…A recent report suggests that constitutive UCP1-Cre mice have leaky Cre expression in other key metabolic tissues such as the hypothalamus and kidney resulting in nonspecific genetic recombination (Claflin et al, 2022). We examined whether the tamoxifen-inducible UCP1-Cre (UCP1 Cre-ERT2) we used resulted in PSD knockout in other tissues.…”
Section: Mitochondrial Pe Is Essential For Brown Adipose Thermogenesismentioning
confidence: 99%